MODERATO Study to Assess the Effect of Rasagiline on Patients With Parkinson Disease and Mild Cognitive Impairment - Vinall, Maria (MD Conference Express, 2015)
Parkinson disease (PD) with mild cognitive impairment (PD-MCI) is relatively common in nondemented PD patients, but currently there is no approved treatment. The phase 4 MODERATO is evaluating the effect of 24 weeks of treatment with rasagiline 1 mg/d as add-on therapy in adults with PD-MCI. The trial, which has enrolled 170 patients, is the largest to date to evaluate a treatment for PC-MCI.